Bilateral Adrenal Hyperplasia Due to Adrenocorticotropic Hormone–Secreting Esthesioneuroblastoma on FDG PET and 111In-Pentetreotide Scintigraphy. (June 2018) - Matsusaka, Yohji; Nakahara, Tadaki; Kurihara, Isao; Iwabuchi, Yu; Jinzaki, Masahiro
Abstract : Abstract: A 53-year-old woman with metastatic esthesioneuroblastoma was referred for FDG PET/CT imaging. FDG PET/CT showed symmetrical uptake in bilaterally enlarged adrenal glands, in addition to abnormal uptake in bone and lymph node metastases. 111 In-pentetreotide scintigraphy was further performed and revealed the lack of adrenal uptake. The patient's serum adrenocorticotropic hormone (ACTH) level was extremely high, suggesting that hyperplastic condition in the adrenal glands due to ACTH stimulation from the metastatic esthesioneuroblastoma was responsible for increased FDG uptake. The combination of FDG PET and 111 In-pentetreotide scintigraphy was useful for the pathophysiological evaluation of ACTH-secreting esthesioneuroblastoma.